Scenario-guided policy planning in Uganda and Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Policy makers from Tanzania and Uganda came together for two back-to-back workshops in the region. The activities focused on scenario-guided policy development in the context of climate change, and covered Tanzania’s New Environmental Policy, and in Uganda the National Agricultural Policy and revising the Mechanization Framework. This workshop is part of the Policy Action for Climate Change Adaptation (PACCA) project, led by International Institute for Tropical Agriculture (IITA), supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). The workshops were organised in collaboration with the University of Oxford. Video by Elizabeth van de Grift.